Cervical disc arthroplasty for symptomatic cervical disc disease: Traditional and Bayesian meta-analysis with trial sequential analysis. (November 2016) - Kan, Shun-Li; Yuan, Zhi-Fang; Ning, Guang-Zhi; Liu, Fei-Fei; Sun, Jing-Cheng; Feng, Shi-Qing
Abstract: Objective: Cervical disc arthroplasty (CDA) has been designed as a substitute for anterior cervical discectomy and fusion (ACDF) in the treatment of symptomatic cervical disc disease (CDD). Several researchers have compared CDA with ACDF for the treatment of symptomatic CDD; however, the findings of these studies are inconclusive. Using recently published evidence, this meta-analysis was conducted to further verify the benefits and harms of using CDA for treatment of symptomatic CDD. Methods: Relevant trials were identified by searching the PubMed, EMBASE, and Cochrane Library databases. Outcomes were reported as odds ratio or standardized mean difference. Both traditional frequentist and Bayesian approaches were used to synthesize evidence within random-effects models. Trial sequential analysis (TSA) was applied to test the robustness of our findings and obtain more conservative estimates. Results: Nineteen trials were included. The findings of this meta-analysis demonstrated better overall, neck disability index (NDI), and neurological success; lower NDI and neck and arm pain scores; higher 36-Item Short Form Health Survey (SF-36) Physical Component Summary (PCS) and Mental Component Summary (MCS) scores; more patient satisfaction; greater range of motion at the operative level; and fewer secondary surgical procedures (all P < 0.05) in the CDA group compared with the ACDF group. CDA was not significantly different from ACDF in the rate of adverse events (P > 0.05). TSA of overall success suggested that the cumulative z-curve crossed both the conventional boundary and the trial sequential monitoring boundary for benefit, indicating sufficient and conclusive evidence had been ascertained. Conclusions: For treating symptomatic CDD, CDA was superior to ACDF in terms of overall, NDI, and neurological success; NDI and neck and arm pain scores; SF-36 PCS and MCS scores; patient satisfaction; ROM at the operative level; and secondary surgical procedures rate. Additionally, there was no significant difference between CDA and ACDF in the rate of adverse events. However, as the CDA procedure is a relatively newer operative technique, long-term results and evaluation are necessary before CDA is routinely used in clinical practice. Highlights: Whether cervical disc arthroplasty is superior to ACDF for symptomatic cervical disc disease remains controversial. We have compared cervical disc arthroplasty with ACDF in treatment of symptomatic cervical disc disease. The trial sequential analysis is applied to test the robustness of our findings and get more conservative estimation. According to the results, cervical disc arthroplasty is superior or equivalent to ACDF for cervical disc disease.